Timothy Riese The Conditional Sentence in the Ugrian, Permian and Volgaic Languages; Arvo Laanest Einführung in die ostseefinnischen Sprachen - Suihkonen, Pirkko (Finnisch-Ugrische Forschungen, 1985)
.